QS ENDO Real – A Study by the German Endometriosis Research Foundation (SEF) on the Reality of Care for Patients with Endometriosis in Germany, Austria and Switzerland - Zeppernick, Felix; Zeppernick, Magdalena; Janschek, Elisabeth; Wölfler, Monika; Bornemann, Sebastian; Holtmann, Laura; Oehmke, Frank; Brandes, Iris; Scheible, Chi Mi; Salehin, Darius; Pethick, Sigrid Vingerhagen; Boosz, Alexander Stephan; Krämer, Bernhard; Sillem, Martin; Bühler, Klaus; Keckstein, Jörg; Schweppe, Karl Werner; Meinhold-Heerlein, Ivo; for the QS Endo Working Group of the Endometriosis Research Foundation (SEF) (Geburtshilfe und Frauenheilkunde, 2020)
Endometriosis affects a significant number of young premenopausal women. Quite apart from the medical challenges, endometriosis is a relevant burden for healthcare and social security systems. Standardized quality indicators for the treatment of endometriosis have not previously been systematically verified. The three-stage study QS ENDO was initiated to record and improve the reality and quality of care. One of its aims is to create quality indicators for the diagnosis and treatment of endometriosis. For the first stage of QS ENDO Real, letters were sent to all 1014 gynecological departments in the German-speaking area of Europe (the DACH region) which included a questionnaire as a means of surveying the current state of care. A total of 296 (29.2%) of the centers which received the questionnaire participated in the survey. The subsequent evaluation of the completed questionnaires showed that the majority of patients with endometriosis (around 60%, based on estimates from the data) are not treated in hospitals which have been certified by the SEF. The guidelines recommend the use of specific classification systems (rASRM, ENZIAN) but, depending on the level of care offered by the hospital, only around 44.4 to 66.4% of departments used the rASRM score and only 27% of hospitals used the ENZIAN classification system to describe deep-infiltrating endometriosis. When taking patientsʼ medical history, some centers (6.6 – 17.9%) considered questions about leading symptoms such as dyschezia, dysuria and dyspareunia to be unimportant. QS ENDO Real has made it possible, for the first time, to get an overview of the reality of care provided to patients with endometriosis in the German-speaking areas of Europe. The findings indicate that several of the measures recommended in international guidelines as the gold standard of care are only used to treat some of the patients. In this respect, more efforts will be needed to provide more advanced training. The approach used for treatment must be guideline-based, also in not-certified centers, to improve the quality of care in the treatment of patients with endometriosis.Endometriose betrifft einen großen Teil junger prämenopausaler Frauen und stellt neben den medizinischen Herausforderungen eine relevante Belastung für das Gesundheits- und Sozialsystem dar. Standardisierte Qualitätsindikatoren für die Behandlung der Endometriose wurden bisher nicht systematisch überprüft. Die dreistufige Studie QS ENDO wurde initiiert, um die Versorgungsrealität und -qualität zu erfassen und zu verbessern. Dabei sollen auch Qualitätsindikatoren für die Diagnostik und Therapie der Endometriose generiert werden. In der ersten Stufe QS ENDO Real wurden alle 1014 gynäkologischen Abteilungen im deutschsprachigen Raum (DACH-Region) angeschrieben und die aktuelle Versorgungssituation per Fragebogen ermittelt. An der Erhebung nahmen 296 (29,2%) der angeschriebenen Zentren teil. Bei der Auswertung zeigt sich, dass ein Großteil der Endometriosepatientinnen (ca. 60% basierend auf geschätzten Angaben) nicht in von der SEF zertifizierten Kliniken behandelt wird. Die in den Leitlinien empfohlene Nutzung von Klassifizierungssystemen (rASRM, ENZIAN) wird in Bezug auf den rASRM-Score je nach Versorgungsstufe von 44,4 bis 66,4%, für tief infiltrierende Endometriose (ENZIAN) sogar nur von ca. 27% der Kliniken angegeben. Bei der Anamneseerhebung werden Fragen nach den Leitsymptomen Dyschezie, Algurie und Dyspareunie von einem großen Anteil der Zentren (6,6 – 17,9%) nicht als wichtig beurteilt. Mit QS ENDO Real ist es erstmalig gelungen, einen Überblick der Versorgungsrealität für Endometriosepatientinnen im deutschsprachigen Raum zu erhalten. Die Ergebnisse lassen darauf schließen, dass mehrere der in internationalen Leitlinien als Goldstandard empfohlenen Maßnahmen nur bei einem Teil der Patientinnen durchgeführt werden. Insofern sind weitere Anstrengungen bei der Fort- und Weiterbildung zu fordern. Gerade auch in den nicht zertifizierten Kliniken muss eine leitlinienorientierte Behandlung erfolgen, um die Versorgungsqualität bei der Behandlung von Endometriosepatientinnen zu verbessern.
Keywords: endometriosis; quality assurance; quality of care; care research